Valuasi Saham Perusahaan Subsektor Pharmaceutical and Health Care Research Menggunakan Dividend Discount Model - Kurniawan, Alex Areliano; Esra, Martha Ayerza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This research aims to assess the intrinsic value of stocks of pharmaceutical and healthcare research sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2024 using the Dividend Discounted Model (DDM) method. DDM is a stock valuation method that focuses on the present value of future dividends expected to be received by shareholders. This research uses a descriptive quantitative method with a sample of six companies selected by purposive sampling based on the criteria of paying dividends and having a positive Return on Equity (ROE). Financial statement and stock data were collected from official websites. In applying DDM, this research calculates the dividend growth rate, estimates future dividends, expected returns, and the intrinsic value of the stocks. The results show that three stocks are undervalued and three others are overvalued, with MERK stock being the most recommended to buy as it has the highest difference between its intrinsic value and market price. This research is useful as a consideration for appropriate stock investment in the pharmaceutical and healthcare research sub-sector on the IDX.